Attractiveness and green transition: customer-based destination brand equity and sustainability - Chekalina, Tatiana; Lexhagen, Maria (Mid Sweden University, 2026)
The data has been collected in August-September 2024 as part of BFUF-funded project "Attractiveness and green transition – a web‑based brand experiment for the sustainable development of the hospitality industry". The project (2023-2025) investigated how the sustainability work at the destination is perceived by visitors, what value it creates for them, how destination branding can encourage sustainable behaviour amongst visitors, strengthen the value of the brand and contribute to the green transition of business in the hospitality sector. For more information please see the project report (in Swedish): https://bfuf.se/nyheter/gront-varumarke-ny-rapport-om-hallbarhetsaspekter-i-en-destinations-marknadsforing/

The dataset is the SPSS datafile, which contains values of 76 variables from 1494 respondents of a panel survey. The dataset is used to test the CBDBE model with the sustainability dimension of perceived customer value, as well as moderating effect of ascribed responsibility on the relationship between customer perceived value and tourism destination brand loyalty.
Keywords: Sustainable tourism; Economics and Business; Ekonomi och näringsliv